2020
DOI: 10.1007/jhep07(2020)004
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Nambu monopole in two Higgs doublet models. Cosmological Monopole Collider

Abstract: We study the dynamics of the Nambu monopole in two Higgs doublet models, which is a magnetic monopole attached by two topological Z strings (Z flux tubes) from two opposite sides. The monopole is a topologically stable solution of the equation of motions when the Higgs potential has global U (1) and ℤ2 symmetries. In this paper, we consider more general cases without the ℤ2 symmetry, and find that it is no longer a static solution but moves along the Z string being pulled by the heavier string. After analytica… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 78 publications
0
31
0
Order By: Relevance
“…1. The 2HDM, along with other new physics models, are known to produce other topological defects besides of the domain wall solutions from the CP symmetry, such as vortices and monopoles [52,57,[69][70][71][72][73]. The solutions to these structure can lead to GW signals as well.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…1. The 2HDM, along with other new physics models, are known to produce other topological defects besides of the domain wall solutions from the CP symmetry, such as vortices and monopoles [52,57,[69][70][71][72][73]. The solutions to these structure can lead to GW signals as well.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Since the discovery of the gravitational waves (GW) by the LIGO/Virgo collaboration [5,6], it is widely believed that the further probes of various GW signals in different frequencies can provide an unprecedented window to the new physics beyond the SM. It is likely that the symmetry breaking patterns in new physics models are associated with non-trivial vacuum structure, which therefore leads to various topological defects [7][8][9][10][11][12][13]. The GWs from different topological defects during the early evolution of the Universe have been studied in many early literatures as well as recent ones, such as domain walls [14][15][16][17][18][19][20][21][22][23] and cosmic strings [3,14,15,[24][25][26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…In refs. [62,64], it is shown that, in 2HDM, the smaller (larger) value of α 3 tends to make the tension of the string with the W -flux heavier (lighter) than that of the string with the Z-flux. Thus, in our case, we expect that the type-C string is lighter than the type-A and type-B ones when α 3 is larger than a critical value depending on other parameters.…”
Section: Jhep06(2021)172mentioning
confidence: 99%
“…The electroweak string is a string containing flux tubes of the SU(2) W × U(1) Y gauge fields like the Abrikosov-Nielsen-Olesen vortex [41,42] and has been studied in the SM [43][44][45][46][47][48][49][50][51] (see ref. [52] for review), and in two Higgs doublet models (2HDM) [53][54][55][56][57][58][59][60][61][62] (for recent comprehensive studies, see refs. [63,64]).…”
Section: Introductionmentioning
confidence: 99%